... take up thy bed, and vote: Measuring the relationship between voting behaviour and indicators of health - Kevin Denny; Orla Doyle (University College Dublin, UCD School of Economics, 2005)
Individuals experiencing poor health are less likely to vote at election time, despite being the ones most affected by health policies implemented by the successful party. This paper investigates the relationship between health and voter turnout and political party choice in the 1979, 1987 and 1997 British general elections using the National Child Development Study (NCDS). It finds that poor health is associated with lower turnout, as the perceived costs of voting, such as the physical and mental effort involved, are greater than the perceived benefits, which are derived from the policy implications of the election outcome. In addition, the subset of unhealthy individuals who do vote at election time generally support Labour, as such voters are more likely to utilise the NHS and hence support parties that advocate public provision of health services. Given the low participation rates of the unhealthy, a political party which formulates an attractive policy package aimed at such potential voters could therefore mobilise a previously untapped source of the electorate.
hdl:10197/160
Keywords: 330; Health Status; Voter Turnout; Political Party Choice; Wahlverhalten; Gesundheit; Meinung; Großbritannien